Synthesis of thymosin beta 4 by peritoneal macrophages and adherent spleen cells. - Xu, G J (1982)
Thymosin beta 4, previously identified as a component of thymosin fraction 5 isolated from calf thymus, is synthesized by peritoneal macrophages derived from rats or mice, including cells from nu/nu mice. Identification of thymosin beta 4 containing [35S]methionine was based on its retention time in reverse-phase HPLC and the recovery of radioactivity in peptides generated by mild acid hydrolysis or by digestion with trypsin. Thymosin beta 4 is also synthesized by rat and mouse spleen cells, and evidence is presented for its release from these cells.